Sistem Pendukung Keputusan Pemilihan Penerimaan Beasiswa Berprestasi Menggunakan Metode Elimination Et Choix Traduisant La Realite - Virdyra Tasril (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
Selection of grantee candidates in SMA Negeri 20 Bagan Deli is still done manually. Prospective scholarship recipients are selected based on the criteria determined by SMA Negeri 20 Bagan Deli. One of the best methods used for this problem is the ELECTRE method and is also one of the most effective methods for making multiple decision choices with clear features that are not clear. This method uses conditions where inappropriate alternatives are eliminated to obtain the expected results. Therefore, this method is widely used for cases that have many options but few criteria are involved. This research is expected to provide convenience for the school in determining scholarships on their students. Keywords: Decision Support System, Electre, Scholarship